2020
DOI: 10.1128/jvi.00326-20
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate Reprograms Expression of Specific Interferon-Stimulated Genes

Abstract: Butyrate is an abundant metabolite produced by gut microbiota. While butyrate is a known histone deacetylase inhibitor that activates expression of many genes involved in immune system pathways, its effects on virus infections and on the antiviral type I interferon (IFN) response have not been adequately investigated. We found that butyrate increases cellular infection with viruses relevant to human and animal health, including influenza virus, reovirus, HIV-1, human metapneumovirus, and vesicular stomatitis v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 88 publications
(86 reference statements)
2
38
1
Order By: Relevance
“…This effect was associated with suppression of specific antiviral interferon-stimulated genes. 23 Another study reported an exacerbation of arthropathy-induced by Chikungunya virus in mice after treatment with high-fiber diet or butyrate. 24 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This effect was associated with suppression of specific antiviral interferon-stimulated genes. 23 Another study reported an exacerbation of arthropathy-induced by Chikungunya virus in mice after treatment with high-fiber diet or butyrate. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, one of the main investigations that has been carried out around the world is to dissect how the infection occurs in each tissue and systems and how that tissue reacts to the presence of this infection, especially in patients who already have an inflammatory condition, such as obesity. 23 , 28 , 29 A study with intestinal and pulmonary epithelial cell lines showed that SARS-CoV-2 infection alters the expression of inflammatory cytokines and anti-viral molecules such as IFNα and IFNÎČ in lung cells. Their findings suggested the pre-activation of IFN-I signaling pathway as a potential therapeutic and prophylactic management for COVID-19 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, increased serum levels of these metabolites have been found in patients with this condition and it is notable that diarrhea is one of the symptoms that is common to both COVID and IBS 29 . In addition, high levels of butyric acid have been thought to promote viral replication and interfere with the interferon response 30 . Therefore, the dysregulation of gut microbiota, expressed by various gastrointestinal symptoms and an altered pro le of microbial metabolites, underscores the potential relevance of dietary interventions to prevent the progression of COVID-19 severity.…”
Section: Discussionmentioning
confidence: 99%
“…Immunomodulatory signals by the gut microbial community can also alter susceptibility to nonenteric infections. Production of the short-chain fatty acid butyrate by enteric commensals can lead to a systemic suppression of IFN production and interferon responsive gene expression and increase susceptibility to influenza virus, reovirus, HIV-1, human metapneumovirus, and vesicular stomatitis virus (126). Alteration of the gut microbial community during an IAV infection can alter the production of another short-chain fatty acid, acetate, reducing bactericidal activity of alveolar macrophages and enhances susceptibility to bacterial pneumonia (127).…”
Section: Polymicrobial Impacts On Acquisitionmentioning
confidence: 99%